Studies on Somnolence in the Daytime Caused by Drugs Used for Neuropathic Pain - Yasuhiro Takeda; Takayuki Ishida; Ryuki Tsutsui; Katsuo Toide; Sachi Tanimoto-Mori; Shuzo Watanabe; Yoshihito Kanai; Chiaki Kamei (Elsevier, 2008)
In the present study, the characteristics of the sleep features of amitriptyline, mexiletine, and N-(4-tertiarybutylphenyl)-4-(3-cholorphyridin-2-yl)tetrahydropyradine-1(2H)-carbox-amide (BCTC) were studied. Electrodes were chronically implanted into the frontal cortex and the dorsal neck muscles of rats for electroencephalogram (EEG) and electromyogram (EMG) measurements, respectively. EEG and EMG were recorded with an electroencephalograph, and SleepSign ver. 2.0. was used for sleep-wake state analysis. Recordings were performed from 11:00 to 17:00. Amitriptyline caused significant decreases in sleep latency and total wake time and an increase in total non-rapid eye movement (non-REM) sleep time. Mexiletine caused a significant decrease in sleep latency, but no significant effect was observed in total wake time and total non-REM sleep time. On the other hand, BCTC, which is an antagonist of transient receptor potential vaniloid 1 (TRPV1), showed no significant effect on sleep latency, total wake time, total non-REM sleep time, and total REM sleep time. From these results, it can be concluded that a TRPV1 antagonist may become a useful drug for neuropathic pain without sedative side effects in the daytime, different from amitriptyline and mexiletine. Keywords:: amitriptyline, mexiletine, TRPV1 antagonist, somnolence